Peraturan Warisan Budaya dan Morfologi Sektoral Transformasi Perkotaan di Kawasan Kolonial Asia-Afrika Bandung - Andiyan Andiyan; Dimas Wihardyanto (Universitas Sebelas Maret Surakarta, 2026)
Cultural Heritage Regulations and Urban Transformation Sectoral Morphology in Bandung's Asian-African Colonial DistrictThe Asia-Africa district of Bandung must reconcile colonialism and modernity. The 2009–2025 cultural identity conservation measures of Bandung are criticized in worldwide urban heritage disputes. Qualitative-descriptive methods included field observations, photography, historical colonial maps, and morphological analysis using Homer Hoyt's sectoral model and Lefebvre's spatial theory Alun-Alun to inclusive social space sectoral growth is shown by layered maps (1826–1987). Results indicate regulatory movement from conservative to integrative, UNESCO Historic Urban Landscape compliance, legal consistency, and community participation difficulties. The Bandung urban heritage lab supports identity-driven, sustainable city development.